Improving In-Situ Sodium Metal Plating on Copper Foil Through Optimization of Mechanical Pressure: Towards High-Performance Anode-Free Sodium Ion Batteries - Willow, Ashley; Hussein, Haytham E. M.; Vajirakaphan, Sutthiphan; Chasri, Aphidet; Margadonna, Serena (Frontiers in Energy Research, 2022)
Herein we report key developments on the scale-up of sodium ion anode free batteries through investigation of the effects of applied external pressure cell performance. Sodium ion anode free puts extra emphasis on high plating and stripping efficiency of sodium metal at the anode surface, due to the lack of an excess of the transporting ion. We demonstrate excellent Na||Cu half-cell results in coin cell configuration, and the scalability of the anode-free concept is further demonstrated, by plating and stripping of sodium metal on copper foils 10-fold larger (>10 cm 2) than in other studies in coin cells (~1cm2). It is discovered that pressure is paramount in establishing dendrite free sodium deposition at this scale through investigating the half-cell cycling at 56-743 kPa. Achieving a low hysteresis in these large-area cells is found to only require moderate pressures (~185 kPa). However, achieving a high cycle life required increasing the pressure to 743 kPa. It is only at these high pressures that non-dendritic sodium deposition is demonstrated due to a homogeneous plating distribution enabled by proper contact between electrodes, as confirmed by impedance measurements and optical imaging of the deposited sodium.